Challenges for sustainable solid waste management : Lessons from Thailand - Pharino, C. (Springer, 2017)
This book analyzes the status quo concerning waste generation and management systems in Thailand and other developing countries with similar problems. It addresses municipal, electronic, industrial and hazardous wastes, as well as management instruments, and key factors shaping the progress of waste management as a whole. The book highlights lessons learnt from various successful efforts to overcome these problems in Thailand, and offers recommendations for promoting sustainable waste management systems in Thailand and other countries with similar backgrounds in the future. These include the introduction of a polluter-pay concept, incentive systems for recycling and reusing, and promoting environmental education and awareness in key sectors.
Keywords: Refuse and refuse disposal -- Thailand.; Refuse and refuse disposal -- Thailand -- Case studies.; Thailand.; elektronické knihy; electronic books